A meta-analysis of the correlation between the duration of the second stage of labor and recent postpartum pelvic floor injury in primiparous - Chen, Yuying; Zhao, Bin; Chen, Zhaoyuan (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to explore the correlation between the duration of the second stage of labor and recent postpartum pelvic floor injury in primiparous women.MethodsRandomized controlled trials (RCTs) were systematically evaluated by a comprehensive literature review and inclusion criteria. This study aimed to evaluate the correlation between the duration of the second stage of labor and recent postpartum pelvic floor dysfunction in primiparous women. The quality of the included studies was assessed using the Cochrane risk of bias tool, and meta-analysis was performed using RevMan 5.3 software. Primary outcome measures included pelvic organ prolapse (POP), urinary incontinence (UI), fecal incontinence (FI), postpartum sexual dysfunction, pelvic floor pain, and urinary retention.ResultsA total of 13 articles were included, comprising 2,862 researchers: 1,407 in the extension group, and 1,455 in the general group. All studies were randomized controlled trials. There was no significant difference in POP between the extension group and the general group [OR = 1.25, 95% CI (0.99–1.59), p = 0.06]. UI was more severe in the extension group [OR = 1.95, 95% CI (1.30–2.92), p = 0.001]. There was no significant difference in FI between the extension and control groups [OR = 1.28, 95% CI (0.98–1.68), p = 0.07]. Postpartum sexual dysfunction was not significantly worse in the extension group than in the control group [OR = 1.67, 95% CI (0.81–3.42), p = 0.16]. Pelvic floor pain was stronger in the extension group [OR = 1.24, 95% CI (1.03–1.50), p = 0.03]. Urinary retention was more severe in the extension group [OR = 2.40, 95% CI (1.12–5.15), p = 0.03].ConclusionThe prolongation of the second stage of labor in primiparous parturients is significantly correlated with recent postpartum pelvic floor dysfunction, including urinary incontinence, pelvic floor pain, and urinary retention. Although no significant differences were observed in pelvic organ prolapse and fecal incontinence, a trend was observed. Postpartum sexual dysfunction did not show a significant correlation with prolonged labor.